Pola Komunikasi dalam Penentuan Hari Pernikahan Suku Bugis di Kabupaten Sinjai - Nawir, Magfirah; Sultan, Moeh Iqbal; Kahar, Kahar (LP2M IAIN Palopo, 2024)
This study aims to analyze communication patterns in determining the wedding day of the Bugis tribe in Sinjai Regency. The method used in this research is qualitative research method. Data collection techniques used include observation, interviews, literature studies. The data sources used are primary data and secondary data. Data analysis includes data processing, interpretation, and presentation to reach conclusions. The results of this study indicate that the communication patterns used in this case are separate balanced communication patterns, namely the two families who will hold a wedding carry out a balanced and separate communication pattern, where each family appoints a person who is considered an elder to organize everything (pabbicara / spokesman). An equal communication pattern is where both families can consider each other's needs and preferences to determine a suitable wedding day for both parties. This is done by listening to each other, respecting and appreciating each other's opinions. Linear communication pattern: Traditional leaders who have knowledge of the Bugis calendar system (kutika bilangeng) convey messages to the spokesperson of the family in a passive or one-way manner. This research provides an in-depth insight into how communication patterns in determining the wedding day of the Bugis tribe in Sinjai Regency. Kutika Bilangeng or the traditional calendar system is the first step taken by the Bugis community in determining the wedding day, with the belief that choosing a good time can bring blessings and luck.